KEKUATAN MENGIKAT RISALAH LELANG TERHADAP HAK TANGGUNGAN BAGI PEMBELI LELANG DI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) MEDAN - IRFAN HAMZAH MANGUNSONG (Ilmu Hukum Prima (IHP), 2020)
Creditors as bidders of hypothecation object frequently encounter obstacles such as: the auction objectclearance is impeded by debtor’s or third party’s resistance, debtor’s denial for havingneglected his duty to the creditor, creditor’s statement that it is not the time for creditor to execute the mortgage, and debtor’s denial to the amount of debt including all costs previously expended by creditor for the hypothecation. The research used descriptive analytic method with juridical empirical approach. The data were sourced from secondary data. This research was conducted at KPKNL, Medan as the research location. The data were collected by conducting library research and field research. The data were collected through document study or library research and interviews. The instruments used to collect data consisted of document study or library research and interview. The datawere analyzed by using qualitative data analysis method. The conclusion was drawn deductively. The result of the research demonstrates that auction minutes are an authentic deed which has complete evidence force. Any obstacles encountered and efforts made by KPKNLto overcome the obstacles in implementing foreclosure sale on hypothecation in KPKNL have to be well handled, and auction bidders who have good faith have to be protected by the law.